2019
DOI: 10.21203/rs.2.11005/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prepared for PrEP: Preferences for HIV pre-exposure prophylaxis among Chinese men who have sex with men in an online national survey

Abstract: Background: Pre-exposure prophylaxis (PrEP) is not widely available in China. Previous studies reported low awareness and inconclusive findings on the acceptability of PrEP among Chinese men who have sex with men (MSM). Methods: We conducted a secondary analysis of an online national survey comparing preferences for oral and long-acting injectable PrEP among MSM and identifying correlates of preferences. The study did not collect detailed information about partner types that may influence negotiated safety and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In this cohort that studied oral PrEP preference, uptake, adherence and continuation, nearly half of AGYW preferred oral PrEP to other biomedical prevention methods, but uptake, adherence and PrEP continuation were low. Studies among men who have sex with men (MSM) show that 25–36% prefer oral PrEP to other options, including those in development, that is condoms, LA injectable PrEP and PrEP implants [16, 17]. A review of qualitative data from potential PrEP users, including AGYW, highlights that individual “preference” to use oral PrEP depends on how conveniently it can be incorporated into everyday life [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this cohort that studied oral PrEP preference, uptake, adherence and continuation, nearly half of AGYW preferred oral PrEP to other biomedical prevention methods, but uptake, adherence and PrEP continuation were low. Studies among men who have sex with men (MSM) show that 25–36% prefer oral PrEP to other options, including those in development, that is condoms, LA injectable PrEP and PrEP implants [16, 17]. A review of qualitative data from potential PrEP users, including AGYW, highlights that individual “preference” to use oral PrEP depends on how conveniently it can be incorporated into everyday life [18].…”
Section: Discussionmentioning
confidence: 99%
“…The median (IQR) time on PrEP was 2.52 months. Fifty-five volunteers discontinued PrEP as follows: lost to follow up (17), side effects (12), no longer interested or lower perceived HIV risk (9) and other reasons, for example pill burden, stigma (17). Four of these re-started, therefore, 30 volunteers (37.0%) completed the study on PrEP.…”
Section: Retention Of 265 Agyw Who Were Offered Prep (2019-2020)mentioning
confidence: 99%
“…This demonstrates that expanded PrEP or PEP knowledge dissemination in recent years was effective in increasing relative awareness, yet efforts of promoting the uptake saw little improvement among MSM in China. Previous studies showed that awareness of PrEP was associated with potential PrEP uptake (10,14). Increasing accurate knowledge for PrEP could promote PrEP initiation among MSM in China (12).…”
Section: Discussionmentioning
confidence: 97%
“…Although studies about acceptability from LMIC indicate a preference for long-acting prevention methods generally, these did not specifically consider LA-CAB and its specific logistical considerations for service delivery, which will require more human and financial resources, and will increase costs [39,43,44].…”
Section: Preexposure Prophylaxis Service Delivery Modelsmentioning
confidence: 99%